2021
DOI: 10.1002/cpt.2227
|View full text |Cite
|
Sign up to set email alerts
|

Successful Prediction of Human Steady‐State Unbound Brain‐to‐Plasma Concentration Ratio of P‐gp Substrates Using the Proteomics‐Informed Relative Expression Factor Approach

Abstract: Accurately predicting unbound brain interstitial fluid (ISF) concentrations of CNS drugs is challenging, especially when drugs are substrates of efflux transporters (e.g., P-glycoprotein). This is one reason why development of CNS drugs has a high attrition rate. WHAT QUESTION DID THIS STUDY ADDRESS?  We determined whether the proteomics-informed relative expression factor (REF) approach can successfully predict the unbound human brain ISF distribution of drugs at steady state or pseudoequilibrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…Before an approach can be used with confidence, it must be validated with additional transporter substrates for key transporters important in drug disposition/distribution and the corresponding tissue concentrations obtained by PET imaging. In this regard, we have already validated the ability of the REF approach to predict the unbound tissue‐to‐plasma concentration ratio of human brain and fetus (at term) for MDR1 substrate drugs 30,31 . Thus, we propose that the REF approach can now be used with confidence to predict tissue drug concentrations when transporters are present at the tissue‐blood barrier provided these transporters are known and can be quantified in the tissue of interest.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Before an approach can be used with confidence, it must be validated with additional transporter substrates for key transporters important in drug disposition/distribution and the corresponding tissue concentrations obtained by PET imaging. In this regard, we have already validated the ability of the REF approach to predict the unbound tissue‐to‐plasma concentration ratio of human brain and fetus (at term) for MDR1 substrate drugs 30,31 . Thus, we propose that the REF approach can now be used with confidence to predict tissue drug concentrations when transporters are present at the tissue‐blood barrier provided these transporters are known and can be quantified in the tissue of interest.…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, we have already validated the ability of the REF approach to predict the unbound tissue-to-plasma concentration ratio of human brain and fetus (at term) for MDR1 substrate drugs. 30,31 Thus, we propose that the REF approach can now be used with confidence to predict tissue drug concentrations when transporters are present at the tissue-blood barrier provided these transporters are known and can be quantified in the tissue of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al, 2021;V. Kumar et al, 2018;Sachar et al, 2020;Storelli et al, 2021;Trapa, Belova, Liras, Scott, & Steyn, 2016;Trapa et al, 2019). In conclusion, our study provides a tool to prospectively predict the fetal exposure to drugs at various gestational ages to help assess potential fetal benefits and risks associated with maternal drug administration.…”
Section: B-d 3 B-d)mentioning
confidence: 85%
“…Therefore, to make our m-f PBPK model comprehensive, we combined it with the efflux ratio-relative expression factor approach (ER-REF) to predict fetal K p,uu of drugs that are actively transported by the placenta. The ER-REF approach to predict K p,uu has been described previously to predict brain distribution of transporter substrates in humans and preclinical species (Storelli, Anoshchenko, & Unadkat, 2021;Trapa et al, 2019;Uchida, Ohtsuki, Kamiie, & Terasaki, 2011;Uchida et al, 2014). It relies on measurement of 1) transport clearance of the drugs (i.e., via the efflux ratio, ER) in transporter-overexpressing cell lines (e.g., Transwell®) and 2) transporter abundance in both in vivo tissue (the placenta) and transporteroverexpressing cell lines using quantitative targeted proteomics to obtain REF (see, Figure 1 for workflow).…”
Section: Introduction (804/750 Words)mentioning
confidence: 99%
“…It has been reported that one of the crucial causes of MDR in cancer is P-gp–mediated efflux transportation of chemotherapeutic drugs ( 25 ). In this study, P-gp was highly expressed in drug-resistant CIA-FLS/MTX cells.…”
Section: Discussionmentioning
confidence: 99%